Islam, Modernity, Violence, and Everyday Life - Ahmad, A. author. aut Link
VIII, 213 p.
Keywords: This book offers a better insight into the comparison of Western and Islamic cultures, with studies that address the issues of Islam and modernity, violence in Islamic law and history, and respect for individuals' privacy in Islamic cultures.